Towards rational decision making in antimicrobial therapy. An annotated bibliography - Smith P. (The use of veterinary drugs and vaccines in Mediterranean aquaculture, 2009)
An overview of the recent progress made during the period 2003-2008 for the determination of the susceptibility to antimicrobials of bacteria associated with fish diseases is provided in the form of an annotated bibliography. Some key papers related to current practice, epidemiological cut-off values, the disc diffusion test protocol and antimicrobial susceptibility are briefly outlined.
The Use of Veterinary Drugs and Vaccines in Mediterranean Aquaculture, 2003/05/21-23, Izmir (Turkey)